2021
DOI: 10.1002/cssc.202100848
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Anion Interactions with Ag Electrodes on Electrochemical CO2 Reduction in Choline Halide Electrolytes

Abstract: Interactions of electrolyte ions at electrocatalyst surfaces influence the selectivity of electrochemical CO2 reduction (CO2R) to chemical feedstocks like CO. We investigated the effects of anion type in aqueous choline halide solutions (ChCl, ChBr, and ChI) on the selectivity of CO2R to CO over an Ag foil cathode. Using an H‐type cell, we observed that halide‐specific adsorption at the Ag surface limits CO faradaic efficiency (FECO) at potentials more positive than −1.0 V vs. reversible hydrogen electrode (RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…This description originates from (1) the fact that CO2RR requires the CO2 and protons as reactants and a sink for liquid products and (2) the common observation of enhanced CO2RR reactivity and selectivity over CLs with a moderate increase of hydrophobicity. [126][127][128][129][130] For example, Shi et al 137 Nevertheless, this work is a step forward in understanding the ideal wetting conditions of CL for CO2RR experimentally. Nevertheless, the triple-phase boundaries' role in CO2RR or even the TPB locations in the GDEs (i.e., either within the CL or at the CL -GDL interfaces) are not explicitly described.…”
Section: Desired Wetting Conditions For Co2rr Gas-diffusion Cathodesmentioning
confidence: 97%
See 3 more Smart Citations
“…This description originates from (1) the fact that CO2RR requires the CO2 and protons as reactants and a sink for liquid products and (2) the common observation of enhanced CO2RR reactivity and selectivity over CLs with a moderate increase of hydrophobicity. [126][127][128][129][130] For example, Shi et al 137 Nevertheless, this work is a step forward in understanding the ideal wetting conditions of CL for CO2RR experimentally. Nevertheless, the triple-phase boundaries' role in CO2RR or even the TPB locations in the GDEs (i.e., either within the CL or at the CL -GDL interfaces) are not explicitly described.…”
Section: Desired Wetting Conditions For Co2rr Gas-diffusion Cathodesmentioning
confidence: 97%
“…Section 3.1 provides a detailed discussion of the effects of liquid properties such as pH and ion types on the electrode wetting conditions. Additionally, an electric field can effect surface chemistry 125,126 and morphology [127][128][129][130][131][132] of the solid phase, which will impact wetting conditions. Yang et al's 75 reported such effects observed in experiments with X-ray photoelectron spectra to detect the loss of C-F bonds and increase in the concentration of oxygen species at the GDL surface after exposure to cathodic conditions, and this effect may explain the loss of the wettability in the CLs.…”
Section: Static Wetting and Capillary Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…introduced different halide solutions as the catholyte for CO 2 R toward CO over polycrystalline Ag foil. [ 197 ] It turned out that the FE of CO increases in the order of Cl − > Br − > I − at the potential window of > −1.0 V versus RHE. Besides the electronic effect, halide ions can also induce significant surface restructuring to the metal surfaces during CO 2 R, and further lead to changes in the reaction activity and selectivity.…”
Section: Influence Of the Reaction Environments On Co2rmentioning
confidence: 99%